Coupling Aptamer‐based Protein Tagging with Metabolic Glycan Labeling for In Situ Visualization and Biological Function Study of Exosomal Protein‐Specific Glycosylation. (9th July 2021) - Zhu, Lin; Xu, Yuanfeng; Wei, Xinyu; Lin, Haoting; Huang, Mengjiao; Lin, Bingqian; Song, Yanling; Yang, Chaoyong
Abstract: Exosomal glycoproteins play important roles in many physiological and pathological functions. Herein, we developed a dual labeling strategy based on a protein‐specific aptamer tagging and metabolic glycan labeling for visualizing glycosylation of specific proteins on exosomes. The glycosylation of exosomal PD‐L1 (exoPD‐L1) was imaged in situ using intramolecular fluorescence resonance energy transfer (FRET) between fluorescent PD‐L1 aptamers bound on exoPD‐L1 and fluorescent tags on glycans introduced via metabolic glycan labeling. This method enables in situ visualization and biological function study of exosomal protein glycosylation. Exosomal PD‐L1 glycosylation was confirmed to be required in interaction with PD‐1 and participated in inhibiting of CD8 + T cell proliferation. This is an efficient and non‐destructive method to study the presence and function of exosomal protein‐specific glycosylation in situ, which provides a powerful tool for exosomal glycoproteomics research. Abstract : A dual labeling strategy for in situ visualization of exosomal protein‐specific glycosylation based on a protein‐specific aptamer tagging and metabolic glycan labeling (ExoAp‐MGL) was used to study the presence and function of exosomal protein‐specific glycosylation. Exosomal PD‐L1 glycosylation is required for the interaction of exoPD‐L1/PD‐1 and inhibition of CD8 + T cell proliferation.